Effect of malic acid supplementation on rumen fermentation, digestibility and methanogenesis in wheat straw sorghum based total mixed diets in vitro - Sirohi, S K; Pandey, Poonam; Singh, B; Goel, Navneet; Mohini, Madhu (The Indian Journal of Animal Sciences, 2012)
An in vitro incubation system was used to evaluate effect of increasing concentration of malic acid at 0, 5, 10 and 15 mM in wheat straw sorghum diets of different roughage (R) and concentrate (C) ratios i.e. high fiber (80R:20C), medium fiber (50R:50C) and low fiber (20R:80C) diets on different rumen fermentation, total gas and methane production and gas kinetics parameters. All the treatment combinations were arranged in 4 × 3 factorial designs with 3 replicates. Feed samples (200 mg) were incubated in 100 ml calibrated glass syringes with 30 ml mixed rumen suspension for 24 h (methane and fermentation parameters) and 96 h for gas kinetics. In vitro dry matter digestibility (IVDMD) was significantly higher at 5 and 10 mM malic acid in almost all type of diets. A significantly increasing trend of partition factor and microbial biomass (mg) content was seen with increasing concentration of malic acid. Methane (mM/g DM) reduction was 47 to 65% in wheat straw sorghum diets. Significant reduction in ammonia- N concentration was noticed, however decreasing trend in protozoa number was seen in all type of diets but differences among diets remainednonsignificant. Potential gas production and rate constant increased in all dietary treatment combinations. The malic acid was significantly able to modify the rumen fermentation parameters which contributed towards reducing the methane production and the effect was variable depending upon different roughage and concentrate ratios.